2021
DOI: 10.1371/journal.pone.0254690
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-resonance-based measurement of electromagnetic fields and conductivity in vivo using single current administration—A machine learning approach

Abstract: Diffusion tensor magnetic resonance electrical impedance tomography (DT-MREIT) is a newly developed technique that combines MR-based measurements of magnetic flux density with diffusion tensor MRI (DT-MRI) data to reconstruct electrical conductivity tensor distributions. DT-MREIT techniques normally require injection of two independent current patterns for unique reconstruction of conductivity characteristics. In this paper, we demonstrate an algorithm that can be used to reconstruct the position dependent sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…It is an imaging technique that reconstructs the conductivity distribution inside the subject using magnetic flux density or current density measurements acquired by a magnetic resonance imaging system ( 14 , 15 ). Algorithms are currently being developed to optimize the use of acquired images to reconstruct electric field and current density distributions ( 21 ). In a similar way, MR- electrical properties tomography (EPT) non-invasively images the conductivity and permittivity maps in vivo from the radiofrequency field signals obtained with MRI.…”
Section: Techniques Of Measuring Bioimpedance Of Intracranial Tissuesmentioning
confidence: 99%
“…It is an imaging technique that reconstructs the conductivity distribution inside the subject using magnetic flux density or current density measurements acquired by a magnetic resonance imaging system ( 14 , 15 ). Algorithms are currently being developed to optimize the use of acquired images to reconstruct electric field and current density distributions ( 21 ). In a similar way, MR- electrical properties tomography (EPT) non-invasively images the conductivity and permittivity maps in vivo from the radiofrequency field signals obtained with MRI.…”
Section: Techniques Of Measuring Bioimpedance Of Intracranial Tissuesmentioning
confidence: 99%
“…Initial successful MRCDI studies in phantoms, animals, and human limbs in vivo 13–31 formed the basis for more recent in vivo measurements in human brain 32–36 . However, accurate current flow mapping in the brain remains very challenging for several reasons: First, because the measured current‐induced magnetic fields are below 1–2 nT due to safety and tolerability limits of about 1–2 mA for the TES currents, 37 thermal and physiological noise as well as instrumental instabilities result in low SNR.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14] Initial successful MRCDI studies in phantoms, animals, and human limbs in vivo [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] formed the basis for more recent in vivo measurements in human brain. [32][33][34][35][36] However, accurate current flow mapping in the brain remains very challenging for several reasons: First, because the measured current-induced magnetic fields are below 1-2 nT due to safety and tolerability limits of about 1-2 mA for the TES currents, 37 thermal and physiological noise as well as instrumental instabilities result in low SNR. Second, the total scan time is limited by the ability of the participant to continuously lie still in the MR scanner.…”
Section: Introductionmentioning
confidence: 99%
“…Quantifications of intrinsic neuronal magnetic fields (NMFs) arising from the excitation of single neurons, subcellular compartments, and multicellular neuronal populations, were carried out computationally by several groups and can determine possibilities for NMF detection without the need for invasive transcranial wiring at the time of recording [10][11][12][13]. These studies informed the interpretation of MEG recordings [7,14] and catalyzed the design of specialized pulse sequences, phantom measurements and distilled preparations for magnetic resonance imaging (MRI) in attempts to detect NMFs volumetrically [15][16][17][18][19]. To date, real-time detection of NMFs by MEG at native in vivo scenarios, in the presence of motion artifacts, and blood flow related electromagnetic disturbances [7,20,21] requires severe averaging of consecutive trials evoking coordinated activity of many neurons, and has not yet been demonstrated convincingly by volumetric modalities [15,22].…”
Section: Introductionmentioning
confidence: 99%